THE HISTORY AND DEVELOPMENT OF JAPANESE POP CULTURE IN SINGAPORE - Drinanda, Mohammad Khaifaz (UI Scholars Hub, 2023)
Singapore has many advantages that can be exploited by Singapore. One of them is with popular culture. Now popular culture is one part of the culture that is being loved by the younger generation. This relates to the younger generation who are advanced in technology and novelty. One of them is from Japan. Japan is now progressing in terms of popular culture, although in general it is still quite low. This discussion will discuss the history of popular culture in Singapore. Then discuss what events can be part of Japanese popular culture in Singapore. The economic and cultural impact also has an impact on the development of Japanese popular culture in Singapore which further shows that Singapore is one of the countries that can be relied upon and spread to the Southeast Asia region.